Shoe Box Product Development Design Based on Consumer Preference - Rossi Septy Wahyuni; Eko Nursubiyantoro; Kristiyani Dwi Agustin (OPSI, 2021)
Climate change which is triggered by a consumptive human culture continues to be a concern for many parties to be tackled. Shoes have become the primary need of urban communities because of their function that cannot be separated from their daily activities. Shoes that are purchased by consumers are usually packaged in cardboard boxes that follow the components of the contents, namely the shoes and accessories inside. In this case, shoeboxes with the right design and function according to consumer preferences will reduce the likelihood that the shoeboxes are thrown into the trash. Although it is not the centre of consumer attention, shoe boxes remain a necessity in the final production process. It is necessary to design and develop a shoebox product that is in accordance with the final function of the shoebox according to consumer interests. This study uses the QFD method which produces quality 1 houses with communication tools in the form of a preliminary questionnaire to 30 respondents and a follow-up questionnaire to 100 respondents. Concept selection was carried out on the eight alternative concepts developed. The shoebox concept chosen to take into account the desires of the consumer will be made with a sporty shoebox standard size of 22.5 x 12.3 x 32.5 cm. The environmentally friendly shoebox can be seen through the installation of plastic straps which are expected to reduce the use of single-use plastics. In addition, the shoebox is made with an innovative design so that users can use it repeatedly as shoe storage or multipurpose box.